The Effect of Instrumented Financial Literacy on Young Generation Stock Investment Decisions: Countering Endogeneity Problem - Purnamasari, Shresta; Fuad, Muhammad; Sofian Maksar, Muhammad; Sudarsana, Sudarsana (Universitas Negeri Semarang, 2025)
Studies show that financial literacy significantly influences financial decisions. Most research assesses current financial literacy based on past decisions, creating an endogeneity problem that leads to biased and inconsistent parameters, as financial literacy may have developed over time. This study examines endogeneity and its effects. It uses the financial condition of the oldest sibling as an instrumental variable to address endogeneity between young people's financial literacy and their decision to join the Government's stock investment program (Program Yuk Nabung Saham) during its early adoption. The respondents are graduate students from a reputable business school in Jakarta. The Control Function method is used to estimate the effect. Findings indicate that instrumented financial literacy significantly affects young people’s stock investment decisions. Individuals with low financial literacy have a minimal probability of investing, while those with all correct financial literacy have a 91.11% probability. Enhancing understanding of this issue will lead to a better basis for decision-making, even though these findings are intended to evaluate something other than that program.